Variation in the host preferences and responses of Ascia monuste orseis Godart (Lepidoptera: Pieridae) to cultivars of collard greens Brassica oleracea (L.) var. acephala - Schlick-Souza, Eunice Claudia [UNESP]; Baldin, Edson Luiz Lopes [UNESP]; Lourencao, Andre Luiz (Springer Heidelberg, 2011)
This work evaluated the preference of Ascia monuste orseis among 29 cultivars of collard greens through free- and no-choice assays using female adults (attractiveness and oviposition) and third-instar larvae (feeding preference), in both laboratory and greenhouse conditions. In free-choice tests with female adults, the L, V, Y, H, A, and Z cultivars produced oviposition non-preference in butterflies. Cultivars R, P, C, and D produced feeding non-preference in third-instar larvae of A. monuste orseis in free- and no-choice tests. Our findings may be useful for genetic improvement focusing on the development of B. oleracea var. acephala cultivars resistant to A. monuste orseis.
Keywords: Great Southern White; Resistance; Collard greens; Brassicaceae